The costs and benefits of environmental sustainability - Ekins, Paul; Zenghelis, Dimitri (Sustainability science, 2021)
The natural science in GEO-6 makes clear that a range and variety of unwelcome outcomes for humanity, with potentially very significant impacts for human health, become increasingly likely if societies maintain their current development paths. This paper assesses what is known about the likely economic implications of either current trends or the transformation to a low-carbon and resource-efficient economy in the years to 2050 for which GEO-6 calls. A key conclusion is that no conventional cost–benefit analysis for either scenario is possible. This is because the final cost of meeting various decarbonisation and resource-management pathways depends on decisions made today in changing behaviour and generating innovation. The inadequacies of conventional modelling approaches generally lead to understating the risks from unmitigated climate change and overstating the costs of a low-carbon transition, by missing out the cumulative gains from path-dependent innovation. This leads to a flawed conclusion as to how to respond to the climate emergency, namely that significant reductions in emissions are prohibitively expensive and, therefore, to be avoided until new, cost-effective technologies are developed. We argue that this is inconsistent with the evidence and counterproductive in serving to delay decarbonisation efforts, thereby increasing its costs. Understanding the processes which drive innovation, change social norms and avoid locking in to carbon- and resource-intensive technologies, infrastructure and behaviours, will help decision makers as they ponder how to respond to the increasingly stark warnings of natural scientists about the deteriorating condition of the natural environment.